Os três pilares comparativos entre subestações convencionais e isoladas a gás - Torres, João Pedro Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
When settling the construction of a high voltage substation, designers, and engineers, during the initial planning stage, must do several studies focused on the technical and structural characteristics of the installation, to provide a solution for their demand with the best value for money. However, over the years, new ways of designing and building a substation have emerged on the market, including the socalled compact substations, known as Gas-insulated switchgear (GIS), which it is known to have greater structural advantages at medium and long-term compared to conventional ones due to being normally sheltered and immune to weather conditions, however such characteristics also make them less competitive in terms of cost. Therefore, this study proposes a comparative analysis between those layouts (conventional ones and GIS), made through the collection of technical, commercial and reliability data, referring to existing projects, to guide possible requirements decisions, in which not only equipment are compared, but what is closely linked with each solution.

Ao optar pela construção de uma subestação de alta tensão, os projetistas e engenheiros, em fase de projeto, devem realizar diversos estudos focados nas características técnicas e estruturais da instalação, de forma a viabilizar uma solução para a sua demanda com o melhor custo-benefício. No entanto, com o passar dos anos, novas maneiras de projetar e construir uma subestação surgiram no mercado, entre elas as chamadas subestações compactas, conhecidas como Gas-insulated switchgear (GIS), as quais, a priori, apresentam maiores vantagens estruturais a médio e longo prazo frente às convencionais devido a estarem normalmente abrigadas e imunes a intempéries climáticas, contudo tais características também as tornam menos competitivas em termos de custo. Este trabalho propõe uma análise comparativa entre arranjos de subestações ao tempo e GIS, realizada por meio do levantamento de dados técnicos, comerciais e de confiabilidade referentes a projetos já existentes, a fim de orientar possíveis decisões de projeto, nas quais não se compara apenas equipamento com equipamento, mas sim o que está intimamente ligado com cada solução.
The three comparative pillars between conventional and gas insulated substations
Keywords: Gas-Insulated Switchgear; Air-Insulated Switchgear; High Voltage; Substations; Alta Tensão; Subestações; SF6